Computed tomography predictors of progression and re-presentation in uncomplicated diverticulitis: a retrospective study at two regional Australian hospitals - Gichuhi, Robert; Khairilanuar, Norfarehah Binti (International Surgery Journal, 2025)
Background: Acute diverticulitis is a common presentation in Australian hospitals and is primarily assessed with computed tomography (CT). Identifying CT predictors of progression from uncomplicated to complicated diverticulitis, as well as risk factors for re-presentation, is crucial, particularly in regional hospitals with limited interventional radiology services. Methods: This retrospective study included 20 patients with CT-confirmed uncomplicated diverticulitis (WSES Grade 0, Hinchey Stage I) from Bundaberg Base Hospital (BBH) and Hervey Bay Hospital (HBH) between January 2023 and February 2024. Outcomes assessed were progression to complicated diverticulitis and re-presentation within three months. CT features (e.g., free fluid, free air, abscess formation, wall thickening, fat stranding) and clinical variables (e.g., C-reactive protein CRP) were analyzed. Statistical tests included Fisher’s exact test and t-tests, with significance set at p<0.05. Results: Of the 20 patients, 4 progressed to complicated diverticulitis and 16 re-presented with symptoms. Abscess formation was observed exclusively in complicated cases (3/4 vs. 0/16, p=0.003). Free fluid (75.0% vs. 25.0%, p=0.087) and free air (50.0% vs. 6.3%, p=0.081) were more prevalent in complicated cases. Pericolic fat stranding and wall thickening were common but non-specific. Elevated CRP correlated with progression (mean 200.5 vs. 64.5 mg/l, p=0.029). No clear CT predictors were identified for re-presentation, though early cases (<30 days) were likely due to non-resolution and late cases (>30 days, ≤90 days) suggested recurrence. Conclusion: Abscess, free fluid, free air, and elevated CRP (>100 mg/l) were predictors of progression to complicated diverticulitis, with abscess reaching statistical significance. No definitive CT predictors for re-presentation were identified. Structured CT reporting and prioritization of high-risk patients for admission are particularly important in regional settings with inconsistent interventional radiology access.